# Properties of Definite Integrals

• Last Updated : 10 Feb, 2022

An integral which has a limit is known as definite integrals. It has an upper limit and lower limit. It is represented as

#### f(x) = F(b) − F(a)

There are many properties regarding definite integral. We will discuss each property one by one with proof also.

## Properties

### Property 1: f(x) dx = f(y) dy

Proof: f(x) dx…….(1)

Suppose x = y

dx = dy

Putting this in equation (1) f(y) dy

### Property 2: f(x) dx = – f(x) dx

Proof: f(x) dx = F(b) – F(a)……..(1) f(x) dx = F(a) – F(b)………. (2)

From (1) and (2)

We can derive f(x) dx = – f(x) dx

### Property 3: f(x) dx = f(x) dx + f(x) dx

Proof: f(x) dx = F(b) – F(a) ………..(1) f(x) dx = F(p) – F(a) ………..(2) f(x) dx = F(b) – F(p) ………..(3)

From (2) and (3) f(x) dx + f(x) dx = F(p) – F(a) + F(b) – F(p) f(x) dx + f(x) dx = F(b) – F(a) = f(x) dx

Hence, it is Proved.

### Property 4.1: f(x) dx = f(a + b – x) dx

Proof:

Suppose

a + b – x = y…………(1)

-dx = dy

From (1) you can see

when x = a

y = a + b – a

y = b

and when x = b

y = a + b – b

y = a

Replacing by these values he integration on right side becomes f(y)dy

From property 1 and property 2 you can say that f(x) dx = f(a + b – x) dx

### Property 4.2: If the value of a is given as 0 then property 4.1 can be written as f(x) dx = f(b – x) dx

### Property 5: f(x) dx = f(x) dx + f(2a – x) dx

Proof:

We can write f(x) dx as f(x) dx = f(x) dx + f(x) dx  ………….. (1)

I = I1 + I

(from property 3)

Suppose 2a – x = y

-dx = dy

Also when x = 0

y = 2a, and when x = a

y = 2a – a = a

So, f(2a – x)dx  can be written as f(y) dy = I2

Replacing equation (1) with he value of I2 we get f(x) dx = f(x) dx + f(2a – x) dx

### =  0                    ; if f(2a – x) = -f(x)

Proof:

From property 5 we can write f(x) dx as f(x) dx = f(x) dx + f(2a – x) dx  ………….(1)

Part  1: If f(2a – x) = f(x)

Then equation (1) can be written as f(x) dx = f(x) dx + f(x) dx

This can be further written as f(x) dx = 2 f(x) dx

Part  2: If f(2a – x) = -f(x)

Then equation (1) can be written as f(x) dx= f(x) dx – f(x) dx

This can be further written as f(x) dx= 0

### = 0                   ; if a function is odd i.e. f(-x) = -f(x)

Proof:

From property 3 we can write f(x) dx as f(x) dx = f(x) dx + f(x) dx  ………(1)

Suppose f(x) dx = I1 ……(2)

Now, assume x = -y

So, dx = -dy

And also when x = -a then

y= -(-a) = a

and when x = 0 then, y = 0

Putting these values in equation (2) we get

I1 f(-y)dy

Using property 2, I1 can be written as

I1 f(-y)dy

and using property 1 I1 can be written  as

I1 f(-x)dx

Putting value of I1 in equation (1), we get f(x) dx = f(-x) dx + f(x) dx   ……….(3)

Part 1: When f(-x) = f(x)

Then equation(3) becomes f(x) dx = f(x) dx + f(x) dx f(x) dx = 2 f(x) dx

Part  2: When f(-x) = -f(x)

Then equation 3 becomes f(x) dx = – f(x) dx + f(x) d f(x)dx = 0

### Examples

Example 1: I = x(1 – x)99 dx

Solution:

Using  property  4.2 he given question can be written as (1 – x) [1 – (1 – x)]99 dx (1 – x) [1 – 1 + x]99 dx (1 – x)x99 dx = 1/100 – 1/101

= 1 / 10100

Example 2: I = cos(x) log Solution:

f(x) = cos(x) log f(-x) = cos(-x) log f(-x) = -cos(x) log f(-x) = -f(x)

Hence the function is odd. So, Using property f(x)dx = 0; if a function is odd i.e. f(-x) = -f(x) cos(x) log = 0

Example 3: I = [x] dx

Solution: 0 dx + 1 dx + 2 dx + 3 dx + 4 dx  [using Property 3]

= 0 + [x]21 + 2[x]32  + 3[x]43 + 4[x]54

= 0 + (2 – 1) + 2(3 – 2) + 3(4 – 3) + 4(5 – 4)

= 0 + 1 + 2 + 3 + 4

= 10

Example 4: I = |x| dx

Solution: (-x) dx + (x) dx  [using Property 3]

= -[x2/2]0-1 + [x2/2]2

= -[0/2 – 1/2] + [4/2 – 0]

= 1/2 + 2

= 5/2

My Personal Notes arrow_drop_up